2004
DOI: 10.1089/104303404322886093
|View full text |Cite
|
Sign up to set email alerts
|

Redox Regulation of Pancreatic Cancer Cell Growth: Role of Glutathione Peroxidase in the Suppression of the Malignant Phenotype

Abstract: Pancreatic cancer has low levels of antioxidant enzymes including manganese superoxide dismutase (MnSOD), which converts superoxide radical (O(2)(*-)) into hydrogen peroxide (H(2)O(2)), and glutathione peroxidase (GPx), which converts H(2)O(2) into water. Recent studies have demonstrated that overexpression of MnSOD has a tumor-suppressive effect in pancreatic cancer. However, GPx overexpression has been shown to reverse the tumor cell growth inhibition caused by MnSOD overexpression in other types of cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 27 publications
3
72
0
Order By: Relevance
“…Both CLIC1 and CLIC4 are subject to redox regulation with major structural rearrangements and functional activities dependent on redox state (33,34). Because cancer cells frequently exhibit altered redox regulation (35,36), this control of CLIC4 subcellular localization should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Both CLIC1 and CLIC4 are subject to redox regulation with major structural rearrangements and functional activities dependent on redox state (33,34). Because cancer cells frequently exhibit altered redox regulation (35,36), this control of CLIC4 subcellular localization should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, hepatocellular apoptosis was decreased with a resultant increase in dysplastic hepatocytes and these phenotypic changes were likely related to p53 expression. Furthermore, increased ROS activity has been linked to malignant transformation [19] which may be related to cytokine receptor profiles and resistance to apoptosis [20] or to decreased expression of antioxidants [8,21]. In addition to decreasing responsiveness to apoptosis, increased ROS may result in negative regulatory changes in the cell cycle and alter the balance between proliferation and apoptosis [22].…”
Section: Discussionmentioning
confidence: 99%
“…GPx-1 is classified as an antioxidant enzyme and exerts its role to prevent the initiation of cancer by ROS-mediated DNA damage. Previous studies have suggested that GPx-1 is altered in several types of cancer cells (11,12) and overexpression of GPx-1 shows antitumorigenic effect by eliminating oxidants (13). On the other hand, GPx-1 also increases tumorigenesis in transformed cells by limiting apoptotic mechanisms (14,15).…”
Section: Introductionmentioning
confidence: 99%